Informal urban fuelwood markets in South Africa in the context of socio-economic change. (June 2018) - Guild, J.; Shackleton, C.M.
Abstract: In developing countries, fuelwood is important to livelihoods and energy security because it is used for heating, cooking and can provide additional income to households through trade. The global trade in fuelwood is valued between USD 4–26 billion per annum. In South Africa, fuelwood is a widely used domestic energy source; but how that has changed with rapid urbanisation and socio-economic development over the last two decades is unknown. This study examined the presence and nature of urban fuelwood markets in 39 urban areas of the Eastern Cape and Limpopo provinces. Data were collected from 170 informal fuelwood sellers regarding the prevalence, structure, characteristics, and changes over time of the informal fuelwood markets. Over 80% of the sampled towns had an informal fuelwood market and there was a positive relationship between the number of sellers and town population size. For most sellers, the fuelwood trade was their primary occupation and the income earned was supplemented by government social grants. Sellers earned, on average, over US$9 per day. These results show that despite rapid urbanisation and socio-economic development, fuelwood remains an important domestic fuel in towns and cities of South Africa, and an income source for the urban poor. Highlights: Urban fuelwood markets are widespread. Fuelwood markets are persistent in the face of economic and demographic change. Mean income to fuelwood traders are above the poverty line.